Experimental investigation of biopolymers influences on rheology and filtration properties of water-based drilling fluids - Masoud Hadadi; Fahime Kamali; Jeyran Mirhosseininia; Mohammadhashem Shahbazi; Behzad Vaferi (Heliyon)
Pipe-stuck, filtrate volume, and formation damage during the drilling operation are directly related to the poor performance of drilling fluids. Hence, considerable attention is required to improve the filtration and rheological properties of drilling fluids and achieve industrial and environmental qualification standards. This study experimentally investigates the impact of Pectin and Astragalus gum biopolymers on the filtration and rheological properties of the water-based drilling fluid (WBDF). It also compares the results with the base drilling fluid and those obtained by adding commercial xanthan gum to WBDF. Fourier Transform Infrared Spectroscopy, thermogravimetric analysis, Zeta potential, and Scanning Electron Microscopy are applied to characterize these additives. The viscosity, filtrate volume, gel strength, and yield point of these biopolymer-added WBDFs were experimentally measured and compared. Various rheological models have been examined to correlate the experimental data shear stress versus shear rate profiles. Also, the filtration characteristics of WBDF were analyzed at high-temperature and high-pressure conditions using the filter press. The results showed that biopolymer additives considerably improve WBDF performance. The fluid formulations with Pectin presented more advantages over the other two biopolymers regarding fluid cake formation and rheological properties. The WBDF containing xanthan gum, Pectin, and Astragalus gum decreases filtrate volume by 42.9 %, 55.7 %, and 48.6 %, and increases plastic viscosity by 34.4 %, 46.9 %, and 40.6 %, respectively. Also, 56.5 %, 73.9 %, and 78.3 % increases in the yield point of WBDFs were obtained by adding xanthan gum, Pectin, and Astragalus gum to WBDF, respectively. Generally, the viscosity and yield point were more stable for biopolymer additive drilling fluids at high temperatures. In addition, the results showed that adding Pectin would cause less formation damage. The experimental results show that the optimum concentration of xanthan gum, Pectin, and Astragalus gum is 1.4, 1, and 1.05 wt%, respectively.